Shunt Active Power Filter Enhancement Using Advanced Control and Modulation Techniques - Fereidouni, Alireza (Curtin University, 2016)
This thesis aims to enhance the performance of SAPF by proposing advanced techniques: A new frequency locking complex adaptive linear combiner; A new combined particle swarm optimization adaptive linear combiner; A constant frequency space-vector hysteresis control for two-level SAPFs; Extending the previous proposed modulation technique for three-level neutral-point-clamped (NPC) SAPFs; A new five-level adaptive hysteresis-band technique for five-level NPC-based SAPFs; A new adaptive proportional-integral-type fuzzy logic controller fur fast DC voltage control and reference current generation.